Microwave Assistant Synthesis, Antifungal Activity and DFT Theoretical Study of Some Novel 1,2,4-Triazole Derivatives Containing Pyridine Moiety - Sun, Guo-Xiang (Molecular Diversity Preservation International (MDPI), 2014)
In order to investigate the biological activity of novel 1,2,4-triazole compounds, seventeen novel 1,2,4-triazole derivatives containing pyridine moiety were synthesized under microwave assistant condition by multi-step reactions. The structures were characterized by (1)H NMR, MS and elemental analyses. The target compounds were evaluated for their fungicidal activities against Stemphylium lycopersici (Enjoji) Yamamoto, Fusarium oxysporum. sp. cucumebrium, and Botrytis cinerea in vivo, and the results indicated that some of the title compounds displayed excellent fungicidal activities. Theoretical calculation of the title compound was carried out with B3LYP/6-31G (d,p). The full geometry optimization was carried out using 6-31G (d,p) basis set, and the frontier orbital energy, atomic net charges were discussed, and the structure-activity relationship was also studied.